PROBABILITY ANALYSIS OF EXTREME MONTHLY RAINFALL IN BAGHDAD CITY, MIDDLE OF IRAQ - Aboodi, Ali H. Al (Basrah Journal for Engineering Sciences, 2014)
Data sets of highest monthly rainfall for the period (1887-1958) are used for evaluating the proper theoretical statistical distribution of extreme monthly rainfall in Baghdad city. The frequency analyses and most statistical test were done using a commercial version of HYFRAN. Five distributions are used in this research, which are: - Normal, Pearson Type III, Lognormal, 3-parameter lognormal and Gumbel. Estimation of theoretical distribution is achieved by using maximum likelihood method and adequacy test is carried out using chi-square test. Lognormal, 3-parameter lognormal, and Gumbel distributions seem to be suitable for representing of maximum monthly rainfall in the study area.